2010
DOI: 10.1111/j.1442-2042.2010.02469.x
|View full text |Cite
|
Sign up to set email alerts
|

Tension‐free vaginal mesh procedure for pelvic organ prolapse: A single‐center experience of 310 cases with 1‐year follow up

Abstract: Objective: To prospectively evaluate the efficacy of a tension-free vaginal mesh (TVM) procedure for pelvic organ prolapse (POP). Methods: Between December 2005 and April 2008, 310 female patients (mean age 67.2 years, range 42-84) with POP underwent TVM procedures at our institute. Fifty-six individuals were qualified as stage 2 according to the POP quantification system and 162 and 92 were stage 3 and 4, respectively. One hundred ninety-one patients underwent anterior TVM, and seven underwent posterior TVM. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
55
5
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(75 citation statements)
references
References 21 publications
12
55
5
3
Order By: Relevance
“…7 Takahashi et al reported that the anatomical cure rate was 100% after 3 months and 92.3% after 1 year by using a similar (non-mesh-kit) procedure as ours. 8 Our data was as low as their data. Diez-Itza et al reported that preoperative severe prolapse (POP-Q stage III and IV) of any part was associated with anatomical failure but not with functional recurrence.…”
Section: Discussioncontrasting
confidence: 77%
“…7 Takahashi et al reported that the anatomical cure rate was 100% after 3 months and 92.3% after 1 year by using a similar (non-mesh-kit) procedure as ours. 8 Our data was as low as their data. Diez-Itza et al reported that preoperative severe prolapse (POP-Q stage III and IV) of any part was associated with anatomical failure but not with functional recurrence.…”
Section: Discussioncontrasting
confidence: 77%
“…The cumulative continence rate following transobturator mesh was 61 % (81/132) [124][125][126]. However, after the additional insertion of a suburethral tape, 235 out of 237 women (99 %) were continent postoperatively [87,[127][128][129]. One randomized study investigated the question whether treatment should be carried out as a one-stage or a two-stage procedure; it was found that the treatment of stress incontinence was equally successful, irrespective of whether the suburethral TVT was inserted at the same time as the anterior vaginal wall repair (83/87, 95%) or three months later (47/53, 89%; based on an ontreatment analysis) [130].…”
Section: Women With Symptomatic Stress Urinary Incontinence and Genitmentioning
confidence: 99%
“…Bei vernünftiger Indikation und entsprechender operativer Erfahrung bieten die Netze objektiv und auch subjektiv dauerhaft gute Langzeitergebnisse [3] und zeigen randomisiert gegen die klassische vordere Kolporrhaphie bessere Langzeitergebnisse, wenngleich die Kurz-und Langzeitkomplikationsraten der Kunststoffimplantate höher lag [4]. Die oft sehr unkritische Verwendung dieser Netze und von der Industrie getriebene weite Verbreitung, auch bei nicht sehr erfahrenen Operateuren, führte zumindest in den USA 2008 zur Empfehlung seitens der FDA, dass diese Netze aufgrund hoher Komplikationsraten nur bei Rezidiveingriffen indiziert seien.…”
unclassified